2014
DOI: 10.1007/s10461-014-0856-2
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Antiretroviral Drugs in the Illicit Marketplace: Implications for HIV Disease Management Among Vulnerable Populations

Abstract: The diversion of antiretroviral medications (ARVs) has implications for the integrity and success of HIV care, however little is known about the ARV illicit market. This paper aimed to identify the motivations for buying illicit ARVs and to describe market dynamics. Semi-structured interviews (n=44) were conducted with substance-involved individuals living with HIV with a history of purchasing ARVs on the street. Grounded theory was used to code and analyze interviews. Motivations for buying ARVs on the illici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…3234 Increasing evidence also suggests that ARV drugs are shared or channeled into illicit markets in some settings, which could compromise ART adherence and expanded use of PrEP. 32,35,36 More research is needed to understand how Black MSM acquire and use ARV drugs. The findings in this report also indicate an urgent need to educate Black MSM about the appropriate use of ARV drugs, to expand the availability of health services for diagnosing and treating HIV in this population, and to ensure that health services are acceptable and effective for Black MSM.…”
Section: Discussionmentioning
confidence: 99%
“…3234 Increasing evidence also suggests that ARV drugs are shared or channeled into illicit markets in some settings, which could compromise ART adherence and expanded use of PrEP. 32,35,36 More research is needed to understand how Black MSM acquire and use ARV drugs. The findings in this report also indicate an urgent need to educate Black MSM about the appropriate use of ARV drugs, to expand the availability of health services for diagnosing and treating HIV in this population, and to ensure that health services are acceptable and effective for Black MSM.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of ART for sale in illicit markets is not limited to Ethiopia. A study from South Florida found that HIV medicines were for sale in black marketplaces, and reasons for this comprised having limited access to HIV care, to replace lost or ruined medicines, and to have a backup stock [50]. Similarly, a study from South Africa also reported this [51].…”
Section: The Paradoxical Perception That Art Is Expensivementioning
confidence: 99%
“…Even given these limitations, we believe that our findings of misinformation about PrEP among highly vulnerable MSM—together with research describing widespread street markets in ARVs 7,8 —point to important public health policy concerns. First, the diversion and misuse—driven by drug cost—of approved medications to prevent epidemic life-threatening infectious disease would appear to be unprecedented in developed countries.…”
Section: Resultsmentioning
confidence: 86%